An assessment of attitude towards environment: a study of five star hotels in Rajasthan. (2nd April 2020) - Sharma, Smita; Mathur, Naresh Dutt
The environmental attitudes of individuals are an important predictor of their behaviour towards environment. The present study examines the attitudes of hoteliers in Rajasthan towards environment. This research employs the Dunlap and Van Lierre's new ecological paradigm scale to analyse their attitude. The research is primarily exploratory in nature and comprised of 300 top and middle management people. The mean values ranged from 1.54 to 4.52 for odd and even numbered items. Three components have been extracted in the study. The Eigen values for three components extracted are greater than 1 (3.58, 2.00 and 1.757). This explains 73.37% of the variance in communalities. The NEP score in this study was 3.05, which indicates that ecological attitudes among the participating hotels were in accordance with the budding NEP. The study reflects fairly good intentions of the top management which can be translated into an effective environmental management plan for the organisation.